MIND FIELD. - REQUARTH, TIM (Foreign Policy)
The article discusses the science of Neurotechnologies and how along with its advantages this stream of science has a potential for misapplication. Topics include the positive applications of neurotechnologies which includes diagnosing autism or Alzheimer's disease, the findings of a research involving brain-to-brain cooperation of monkeys led by Neuroscientist Miguel Nicolelis, and the potential of this technology to be misapplied like developing bionic soldiers to be used in a war like situation.